2022
DOI: 10.1002/eji.202249948
|View full text |Cite
|
Sign up to set email alerts
|

The thioredoxin system: Balancing redox responses in immune cells and tumors

Abstract: The thioredoxin (TRX) system is an important contributor to cellular redox balance and regulates cell growth, apoptosis, gene expression, and antioxidant defense in nearly all living cells. Oxidative stress, the imbalance between reactive oxygen species (ROS) and antioxidants, can lead to cell death and tissue damage, thereby contributing to aging and to the development of several diseases, including cardiovascular and allergic diseases, diabetes, and neurological disorders. Targeting its activity is also cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…TrxR is a redox protein that maintains the redox ratio of the cellular system 45 . The breast cancer cells express the TrxR redox system 25 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TrxR is a redox protein that maintains the redox ratio of the cellular system 45 . The breast cancer cells express the TrxR redox system 25 .…”
Section: Resultsmentioning
confidence: 99%
“…TrxR is a redox protein that maintains the redox ratio of the cellular system. 45 The breast cancer cells express the TrxR redox system. 25 The inhibition of the TrxR-mediated redox system enhances the cytotoxicity of chemotherapeutic drugs and radiation.…”
Section: Trxr Inhibition In Mda-mb-231 and Mcf-7 Cell Linesmentioning
confidence: 99%
“…In this work, we leveraged the characteristic redox imbalance of AML 25 , 57 , 58 to preferentially adjuvant tumor cells and debris via their exofacial free thiols for in situ vaccination via IV administration. We found that the redox imbalance is further exacerbated by cytarabine treatment, 59 associated with Trx-1 expression, improving binding of our polymer to cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is involved in maintaining the cell’s status and adapting to changes in the redox environment—an essential aspect of many biological processes, including DNA synthesis and repair and cell growth and death. It might have potential therapeutic applications in supporting immune responses under healthy conditions [ 43 ].…”
Section: Discussionmentioning
confidence: 99%